PENERAPAN MODEL 7S MC. KINSEY DI PT. PERKEBUNAN NUSANTARA VII (PERSERO) LAMPUNG (ANALISIS ATAS DAMPAK BUDAYA ORGANISASI BAGI PENINGKATAN KINERJA DI BADAN USAHA MILIK NEGARA) - Department, administratio; Yulianti, Devi (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This research was about the application of 7S Mc Kinsey model at PT. PerkebunanNusantara VII (Persero) Lampung as the analysis of organization culture impact for performanceimprovement in State-Owned Enterprises (SOEs). It was conducted with qualitative approach thataims to describe and analyze the application of 7S Mc Konsey model. The data collection usedthrough documentation by searching and collecting written documents which were relevant to theresearch problem, in the form of documentation of the organization, laws, decisions and documentssupporting research activities. The result showed that the values implemented in that enterprisewas ProMOSI (productivity, quality, organization, service and innovation), the structure was basedon SK Direction No.7.6/Kpts/519/2010 on the 29th November 2010 consisting of 5 districts and 28business units, the annual report contained complete information on the planning, implementationand evaluation of corporate budget usage, the enterprise selected workers consisting of various social and social sciences, using two-way communication, and the strategy used was business success model. The suggestions given to this research were that this SOEs should be more adherent to thebudget in their distribution, create more effective and efficient strategies to improve performance,and alter existing organizational structures. Keywords : 7S Mc. Kinsey model; Organization Culture; Organization Performance